THE METHODS FOR LEARNING POLYSEMANTIC WORDS IN RUSSIAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
One of the most important tasks in the development of speech in school is to streamline vocabulary work, highlight its main directions and justify them, and manage the processes of enriching the vocabulary of schoolchildren. Mastering language, speech is a necessary condition for the formation of a socially active personality. Everyone needs to learn how to express their thoughts well and correctly in oral and written form, to be able to speak and write convincingly and clearly. It is known that one of the indicators of the level of a person's culture, thinking, intelligence is his speech, which must correspond to linguistic norms.